Dynamic Cabin Air Contamination Calculation Theory - Marcel Lakies (Aircraft Design and Systems Group (AERO), Department of Automotive and Aeronautical Engineering, Hamburg University of Applied Sciences, 2019)
In this report an equation is derived to calculate the dynamic effect of primary and secondary aircraft cabin air contamination. The equation is applied in order to understand implications and hazards. Primary contamination is from an outside source in form of normal low level contamination or high level contamination in a failure case. Secondary contamination originates from deposited material released into the cabin by a trigger event. The dynamic effect is described as an initial value problem (IVP) of a system governed by a nonhomogeneous linear first order ordinary differential equation (ODE). More complicated excitations are treated as a sequence of IVPs. The ODE is solved from first principles. Spreadsheets are provided with sample calculations that can be adapted to user needs. The method is not limited to a particular principle of the environmental control system (ECS) or contamination substance. The report considers cabin air recirculation and several locations of contamination sources, filters, and deposit points (where contaminants can accumulate and from where they can be released). This is a level of detail so far not considered in the cabin air literature. Various primary and secondary cabin contamination scenarios are calculated with plausible input parameters taken from popular passenger aircraft. A large cabin volume, high air exchange rate, large filtered air recirculation rate, and high absorption rates at deposit points lead to low contamination concentration at given source strength. Especially high contamination concentrations would result if large deposits of contaminants are released in a short time. The accuracy of the results depends on the accuracy of the input parameters. Five different approaches to reduce the contaminant concentration in the aircraft cabin are discussed and evaluated. More effective solutions involve higher implementation efforts. The method and the spreadsheets allow predicting cabin air contamination concentrations independent of confidential industrial input parameters.
Keywords: Luftfahrt; Luftfahrzeug; Passagierflugzeug; Flugzeugkabine; Luftverschmutzung; Trikresylphosphat; Aeronautics; Airplanes; Air-Pollution; Aircraft cabins; aircraft; cabin; cabin air; ECS; tricresyl phosphate; TCP; initial value problem; IVP; ordinary differential equation; ODE; air; contamination; concentration; contaminant; dynamics; spreadsheet